PENGARUH HARGA DAN DIFERENSIASI PRODUKTERHADAP LABA PENGUSAHA KAFE SE-KOTA BANDUNG - Riska Pasha Sulistio, - (2009)
This research is carried out in caves all over Bandung by enacting manager and supervisor as the respondents. This research intent to find out how big is the impact of price and product differentiation towards profit yielded by cafe entrepreneurs in all over Bandung. The applied research method is survey method. The samples are taken as much as 55 caves in all over Bandung, and the number of respondents is 60 which consisted of both managers and supervisors. Hypothesis testing is carried out by using doubled linear regression analytical technique. Since using data analysis, it is obtained some results as follows: firstly, price influences cafe entrepreneur's profit partially. Second, product differentiation influences cafe entrepreneur's profit partially. And third, both price and product differentiation influence cafe company profit simultaneously. Consequently, it could be concluded that both price and product differentiation partially and simultaneously have positive and significant impact to the cafe entrepreneurs profit in all over Bandung. By that impact the entrepreneurs should be able to give selling price that lower than the competitors, and could increase product differentiation more variant by considering its costs in order that the consumers would not change over at competitors.